(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: This article reveals the essence of growing medicinal plants given At the same time, this article is medicinal in agriculture improvement of the economic basis of plant cultivation proposal aimed at improving the theoretical, legal and methodological foundations and recommendations are given.